2015
DOI: 10.3892/mmr.2015.4329
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of the dipeptidyl peptidase-IV inhibitor, sitagliptin, on non-alcoholic steatohepatitis in FLS-ob/ob male mice

Abstract: Abstract. Non-alcoholic steatohepatitis is characterized by hepatic fat accumulation, inflammation and varying degrees of fibrosis. The dipeptidyl peptidase-IV enzyme is important in glucose metabolism, as well as lipid accumulation, extracellular matrix metabolism and immune stimulation. Furthermore, the enzyme activity of dipeptidyl peptidase-IV is known to be increased in non-alcoholic steatohepatitis. Therefore, dipeptidyl peptidase-IV inhibitors are potential therapeutic agents for non-alcoholic steatohep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
3
14
0
Order By: Relevance
“…The oxidative damage induced by MTX in liver tissue was prevented by sitagliptin pretreatment as it provided anti-oxidant effects not only on the non-enzymatic defense system (GSH), but also on the enzymatic one such as SOD. Similar antioxidant effects of sitagliptin were recently reported in many inflammatory conditions including myocardial injury [12,21], liver steatohepatitis [13,14], type 2 diabetes [22] and renal ischemia/reperfusion injury [23]. …”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The oxidative damage induced by MTX in liver tissue was prevented by sitagliptin pretreatment as it provided anti-oxidant effects not only on the non-enzymatic defense system (GSH), but also on the enzymatic one such as SOD. Similar antioxidant effects of sitagliptin were recently reported in many inflammatory conditions including myocardial injury [12,21], liver steatohepatitis [13,14], type 2 diabetes [22] and renal ischemia/reperfusion injury [23]. …”
Section: Discussionsupporting
confidence: 73%
“…Recently, the anti-inflammatory action of sitagliptin has been reported in different types of cardiovascular injury [1012]. Notably, sitagliptin has shown hepatoprotective activity in experimentally induced steatohepatitis via modulation of lipid metabolism, oxidative stress and inflammatory mediators [13,14]. However, the exact mechanism of its hepatoprotective activity is complex and not completely clarified.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in accordance with the previous studies which showed the ability of sitagliptin to reduce the oxidative burden in different experimental models of organs toxicities. 22,28,42,43 In addition to its direct toxic effects, ROS can induce nuclear transcription factor-kB (NF-kB) activation which leads to its translocation into the nucleus where it binds to the promoter elements and activate the expression of inflammatory cytokine genes with subsequent proinflammatory mediators production such as TNF-a, COX-2, and NO. 7,44 In the current study, DOX administration resulted in the increased expression of NF-kB as well as increased levels of TNF-a and NO.…”
Section: Discussionmentioning
confidence: 99%
“…In rodent models, sitagliptin use has resulted in improved features of NASH [20,37,38] . In humans, randomized controlled trials examining the effect of sitagliptin on liver histology has not previously been examined.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, DPP-IV itself may be important to the pathogenesis of NASH. Use of the DPP-IV inhibitor, sitagliptin, improves lipid metabolism, and attenuates the progression of hepatic fibrosis in mice with NASH, as well as decreases platelet aggregation in vitro [20,21] . Thus, sitagliptin may be an attractive therapeutic option for NASH, especially given its low risk of hypoglycemia, weight-neutrality, and demonstrated safety profile in individuals with moderate hepatic insufficiency [22,23] .…”
Section: Introductionmentioning
confidence: 99%